Clinical Outcomes and Return to Sports After Open Reduction and Hamstring Tendon Autograft Reconstruction in Patients With Acute Traumatic First-Time Posterior Dislocation of the Sternoclavicular Joint. Issue 13 (November 2022) - Tytherleigh-Strong, Graham; Sabharwal, Sanjeeve; Peryt, Adam
Background: Traumatic posterior dislocations of the sternoclavicular joint (SCJ) are rare. Multiple case reports, case series, and systematic reviews have been published on the treatment of posterior SCJ dislocations. However, they have usually been of small numbers, described a variety of surgical techniques on a mixture of acute and chronic dislocations, and have not focused on functional recovery or return to sports. Purpose/Hypothesis: The purpose of this study was to assess the clinical outcomes and return to sports after SCJ open reduction and reconstruction using a hamstring tendon autograft in patients with an acute first-time traumatic posterior dislocation of the SCJ. We hypothesized that SCJ open reduction and reconstruction would result in high survivorship, good clinical outcomes, and a high rate of return to sports. Study Design: Case series; Level of evidence, 4. Methods: This study included all patients who underwent SCJ open reduction and reconstruction within 14 days of sustaining a first-time traumatic posteriorly dislocated SCJ, with a minimum 3-year follow-up. Patient-reported outcomes were assessed by the following scores: short version of the Disabilities of the Arm, Shoulder and Hand (QuickDASH), Rockwood SCJ, modified Constant, and Single Assessment Numeric Evaluation (SANE). Survivorship was defined as no clinical failure, such as instability or recurrent dislocation, and no revision surgery. Return to sports was assessed using a customized questionnaire. Results: A total of 19 patients who underwent surgery were included, with a mean age of 30.8 years (range, 18-52 years). Seventeen patients were available at final follow-up at a mean 94.5 months (range, 37-155 months). At final follow-up, the mean scores were as follows: QuickDASH, 4.3 (range, 0-20.4); Rockwood, 13.9 (range, 12-15); modified Constant, 94.4 (range, 71-100); and SANE, 92.1 (range, 70-100). The construct survivorship was 96%. Of the 14 patients who participated in sports, 12 (86%) returned to their preinjury levels. Conclusion: After an acute first-time traumatic posterior SCJ dislocation, open reduction and stabilization with a hamstring tendon autograft, undertaken within 14 days of injury, provides good clinical outcomes and high rates of survivorship and return to sports.